Participación estudiantil en el proceso de reforma curricular del pregrado de Medicina en la Universidad de Chile: evaluación y desafíos - Troncoso R., Jonathan; Libuy R., Matías; González A., Cristián; Cunill D., Vicente (Revista Hospital Clínico Universidad de Chile, 2014)
In recent years, students have been steadily gaining a much more active role in the process of curriculum reform of undergraduate medical studies which has been conducted at the University of Chile, participating in different stages of curriculum transformation, generating discussion and demanding greater incidence on decision-making arenas. Such participation has led to students’ diagnoses and proposals that have been presented in institutional democratic spaces. Nevertheless, there are still some pending challenges in this reform, like: improving the quality of teaching in all clinical campus, studying and implementing measures to reduce the impact of a negative environment, improving the monitorization of its alumni and the compliance of the graduates’ profile, deepening the process of professionalization of teaching and promoting a democratic culture by encouraging the inclusion of all clinical campus in decision making spaces. Despite all the difficulties identified, ongoing curricular reform process is perceived by the students as an opportunity to move forward in the building of a participatory Medical School, which can respond with excellence to the needs and demands Chile makes to its largest and oldest public university.